A double-decker silsesquioxane of norbornene and performance of crosslinking reactive modified EPDM ablation resistance composites. (February 2023) - Ma, Xutao; Ji, Tiezheng; Zhang, Junan; Shen, Shuai; Wang, Shumeng; Wang, Jian; Hou, Xiao; Yang, Shishan; Ma, Xiaoyan
Graphical abstract: Highlights: A novel Double-Decker Silsesquioxane (DN-DDSQ) of norbornene was designed and synthesized for crosslinking reactive with EPDM. The incorporation of DN-DDSQ into EPDM molecular chains through chemical cross-linked modification can greatly facilitate the mechanical and ablation resistance performance of EPDM and aramid fiber-reinforced EPDM. EPDM ablation resistance composites modified by DN-DDSQ can promote the in-situ transformation of the SiC at lower temperature and further thermal decomposition at higher temperature, absorbing more energy to resist the oxyacetylene torch resulting in improved ablation performance. Abstract: To improve the ablation resistance of ethylene propylene ethylidene norbornene monomer (EPDM) insulation layer, a lightweight novel structure of Double-Decker Silsesquioxane bonded norbornene unit structures (DN-DDSQ) was designed and synthesized for chemically cross-linked with EPDM or cross-linking agent to obtain high performance EPDM ablation resistance composites (DN-DDSQ modified EPDM and DN-DDSQ modified aramid fibers (AF)-reinforced EPDM). The resultant formation of denser cross-linked network and better dispersion of high-temperature resistant cage structure of DDSQ in the EPDM ablation resistance composites can improve its mechanical and ablation performance. Reduction in linear ablation rate of 5 phr DN-DDSQ modified EPDM and AF-reinforced EPDM by 17.15% and 62.40% respectively. Furthermore, the ablation mechanism of DN-DDSQ modified AF-reinforced EPDM was established by the thermochemical transformation and the analysis of the ablated carbon layer. This work will provide new ideas and methods for future reveal the ablation pattern in the ablation process.